2015
DOI: 10.7883/yoken.jjid.2014.467
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Exacerbates Pulmonary Damage in Influenza-Induced Lung Injury

Abstract: SUMMARY:The level of osteopontin (OPN) increases during bacterial lung infection. However, the OPN level in virus-induced lung injury is unclear, and the relationship between the hyer-production of OPN and lung injury remains to be thoroughly understood. Therefore, we sought to determine whether a relationship exists between OPN and pulmonary damage. Particularly, pulmonary edema and the destruction of pulmonary tissue. In this study, we found that the OPN level was significantly elevated in patients with pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…OPN up-regulation in serum and tissue samples from chronic rhinosinusitis and allergic patients also correlated with severity of disease [ 55 , 60 , 61 ]. In agreement with these studies, a recent paper found a positive correlation between increased levels of OPN in human serum and disease severity in influenza patients [ 62 ]. Our in vitro finding suggests that IFN-β reduces the viral infection resulting in decreased IL-1 β and OPN expression and is consistent with previous reports where RSV-A2 infection resulted in significantly higher expression of IFN-α than RSV-L19F in human epithelial cells and BALB/c mice [ 45 , 63 ].…”
Section: Discussionsupporting
confidence: 79%
“…OPN up-regulation in serum and tissue samples from chronic rhinosinusitis and allergic patients also correlated with severity of disease [ 55 , 60 , 61 ]. In agreement with these studies, a recent paper found a positive correlation between increased levels of OPN in human serum and disease severity in influenza patients [ 62 ]. Our in vitro finding suggests that IFN-β reduces the viral infection resulting in decreased IL-1 β and OPN expression and is consistent with previous reports where RSV-A2 infection resulted in significantly higher expression of IFN-α than RSV-L19F in human epithelial cells and BALB/c mice [ 45 , 63 ].…”
Section: Discussionsupporting
confidence: 79%
“… 30 And our previous study inferred MMP7 could play an important role in influenza infection. 31 At 1 month postinfection, we found higher plasma levels of MMP2, MMP3, and MMP9 in survivors of severe H7N9 infection. It is possible that ongoing tissue remodeling adds to the feeble recovery seen after severe H7N9 infection.…”
Section: Discussionmentioning
confidence: 58%
“…There are only a few studies of the relationship between OPN and SHP. OPN can induce a significant increase in the level of tumour necrosis factor α (TNFα) in mice 42 . TNFα can also activate the c-Jun N-terminal kinase (JNK) pathway 43 .…”
Section: Discussionmentioning
confidence: 99%